Transformative Education for Indigenous Students: Culturally Responsive Leadership and Teaching Practices in Educational Institutions - Major, Edmund (City University of Seattle (CityU), 2023)
This capstone paper gives an insight into First Nations educational systems and how educational leadership influences the understanding of First Nations education today. It will suggest how First Nations instructional leaders can be influential leaders in today’s society and how to treat everyone with care. Leaders need to know how to make changes slowly in First Nations schools. The research comprises various peer-reviewed scholarly journals and books from well-known authors, such as Schein. Some topics in this research paper will include the history of First Nations education and educational leadership, transitioning into an effective leader in First Nations Schools, and how to be a caring leader within the school or community. The outcomes will benefit the first-time leader when entering any school. Additionally, this paper will be a guide for use by all instructional leaders.